2D kvazikristali v mehki snovi - Novak, Tadej (Matrika, 2014)
Quasicrystals are ordered self-similar structures without translation symmetry. Beside metal alloys they were also found in soft matter in the last few years, mainly among liquid crystals, nano-particles and colloids. The analogy with two dimensional tilings can help describing them. Properties of quasicrystals differ from ordinary crystalline structures and are opening broad area of new research. Their practical value is being intensively researched, mainly in complex optics and photonics.
Keywords: colloids; crystals; koloidi; kristali; kvazikristali; mehka snov; polimeri; polymers; quasicrystals; soft matter